Studies in Matthew's gospel : literary design, intertextuality, and social setting - Weren, Wilhelmus Johannes Cornelis. (Biblical Interpretation Series, 2014)
These Studies in Matthew's Gospel by Wim J.C. Weren are the result of scholarly work carried out using recent methods in Biblical exegesis such as structural analysis, text semantics and intertextuality. Part One presents a new proposal regarding the macrostructure of Matthew's Gospel and discusses meanings of textual units from this Gospel on the basis of synchronic research. In Part Two, intertextual theories are described and practical tools are developed that enable us to identify various types of relations between texts from Matthew's Gospel and co-generic or co-thematic textual units from the Hebrew Bible, the Septuagint and early Jewish and early Christian writings. Part Three answers the question to what extent the ways in which the disciples are portrayed in Matthew is related to 'real' groups in the Matthean communities. The three successive steps are deliberately chosen and are in a complementary relationship to each other.